Religious Character Formation Through Quran Memorization Program: Pembentukan Karakter Religius Melalui Program Hafalan Al-Quran - Wijayanti, Siti Nadiyatul; Kurniawan, Machful Indra (Indonesian Journal of Islamic Studies, 2025)
Background: Character crisis in Indonesia, including moral degradation among students, highlights the urgency of strengthening religious character from an early age. Specific Background: SD Muhammadiyah 2 Krian implements a structured Quran memorization program to foster religious values in students. Gap: Limited studies explore how systematic memorization programs can comprehensively shape students’ character in elementary schools. Aim: This study aims to describe the implementation of the Tahfidz Quran program as a medium for religious character formation. Method: This phenomenological qualitative research collected data through observation, structured interviews, and documentation with triangulation of sources. Results: Findings show that students develop faith, discipline, responsibility, and tolerance through daily Quran memorization activities after dhuha prayer, supported by parental involvement and school culture. Novelty: This research highlights the integrated model of religious habituation that links school activities, parental support, and teacher guidance. Implications: The study provides practical insights for other schools seeking to implement similar programs for character development. Highlights : Quran memorization fosters students’ faith and discipline School and parents collaboration strengthens religious culture Daily routines create consistent character habituation KeywordReligious Character, Tahfidz Quran, Elementary School, Faith, Discipline